Crop protection - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
The crop protection directory - international edition edited by Elaine Warrell 1997 332pp ISBN 0 951330 3 8 price UKL 125.00 and in developing countries, UKL75.00 which is a special price for readers of Spore.